2021
DOI: 10.3390/app11020793
|View full text |Cite
|
Sign up to set email alerts
|

Optical Design for Laser Diode Scanner Headlamp with Efficiently Distributed Optical Power for Adaptive Driving Beam System of Automobiles

Abstract: The illumination optical system using a laser diode has advantages such as small size and high efficiency compared to an optical system using a conventional light source. In particular, its advantages can be maximized in high-resolution spatial light modulation. Based on these advantages, research to apply laser diode scanning to high-resolution adaptive driving beam (ADB) is currently being actively conducted. To construct a high-resolution illumination optical system for an ADB system using a single laser di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, these SLM-based optics suffer problems of costliness. Moreover, due to the modulate mechanism of global lighting of pixels followed by masking, the optical power of the SLMs that has been shadowed will rapidly heat up the headlight module [ 13 ]. As a result, the optical efficiency decreases as the pixel shadow area increases, leading to a necessity for complex thermal design to prevent the ADB system from overheating damage [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these SLM-based optics suffer problems of costliness. Moreover, due to the modulate mechanism of global lighting of pixels followed by masking, the optical power of the SLMs that has been shadowed will rapidly heat up the headlight module [ 13 ]. As a result, the optical efficiency decreases as the pixel shadow area increases, leading to a necessity for complex thermal design to prevent the ADB system from overheating damage [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…13, 996 5 of 13 around the axis of torsion beams. The intermediate circular gimbal frame that contains the mirror plate and the actuators is supported by a pair of straight beam suspensions of 160 μm in width and 550 μm in length.…”
mentioning
confidence: 99%
“…They managed to attain a spot size radius of 7mm, hence obtaining a uniform laser beam cove. Authors in [2] proposed an optical scanning system wherein they suggested changing the intensity distribution from the center and the edge of the beam using a prism. Authors in [3] used a double Fabry Perot interferometer acoustic sensor to get rid of temperature drifting.…”
Section: Introductionmentioning
confidence: 99%
“…Those predictive technologies could also be applied in mitigating the glare issue for ADB. Choi et al [18] designed laser diode scanning to improve the resolution of ADB; combined with those additional inputs, the non-glare zone can be projected more precisely to avoid glare while maximizing illumination.…”
Section: Introductionmentioning
confidence: 99%